Efficacy and safety of tribendimidine, tribendimidine plus ivermectin, tribendimidine plus oxantel pamoate, and albendazole plus oxantel pamoate against hookworm and concomitant soil-transmitted helminth infections in Tanzania and Côte d'Ivoire: a randomised, controlled, single-blinded, non-inferiority trial. Issue 11 (November 2017) - Moser, Wendelin; Coulibaly, Jean T; Ali, Said M; Ame, Shaali M; Amour, Amour K; Yapi, Richard B; Albonico, Marco; Puchkov, Maxim; Huwyler, Jörg; Hattendorf, Jan; Keiser, Jennifer
Summary: Background: Preventive chemotherapy is the current strategy to control soil-transmitted helminth infections (caused by Ascaris lumbricoides, hookworm, and Trichuris trichiura ). But, to improve efficacy and avoid emerging resistance, new drugs are warranted. Tribendimidine has shown good anthelmintic efficacy and is therefore a frontrunner for monotherapy and combination chemotherapy. Methods: We did a randomised, controlled, single-blinded, non-inferiority trial on Pemba Island, Tanzania, and in Côte d'Ivoire. We recruited adolescents aged 15–18 years from four primary schools on Pemba, and school attendees and non-schoolers from two districts in Côte d'Ivoire. Only hookworm-positive participants were randomly assigned (1:1:1:1) to single, oral doses of tribendimidine 400 mg plus placebo (tribendimidine monotherapy), tribendimidine 400 mg plus ivermectin 200 μg/kg, tribendimidine 400 mg plus oxantel pamoate 25 mg/kg, or albendazole 400 mg plus oxantel pamoate 25 mg/kg. Randomisation was done via a computer-generated list in block sizes of four or eight. Participants were asked to provide two stool samples on 2 consecutive days at baseline and again 14–21 days at follow-up. The primary outcome was the difference in egg-reduction rates (ERRs; ie, the geometric mean reduction) in hookworm egg counts between treatment groups, measured by the Kato-Katz technique. Differences in coadministrated treatment groups were assessed for non-inferiority with a margin of −3% to albendazole plus oxantel pamoate based on the available-case population, analysed by intention to treat. Safety was assessed 3 h and 24 h after treatment. This study is registered with ISRCTN (number 14373201). Findings: Between July 26, and Dec 23, 2016, we treated 636 hookworm-positive participants, and outcome data were available for 601 participants (151 assigned to tribendimidine monotherapy, 154 to tribendimidine plus ivermectin, 148 to tribendimidine plus oxantel pamoate, and 148 to albendazole plus oxantel pamoate). Tribendimidine plus ivermectin was non-inferior to albendazole plus oxantel pamoate (ERRs 99·5% [95% CI 99·2–99·7] vs 96·0% [93·9–97·4]; difference 3·52 percentage points [2·05–5·65]). Likewise, tribendimidine plus oxantel pamoate was non-inferior to albendazole plus oxantel pamoate (ERRs 96·5% [95% CI 94·9 to 97·6] vs 96·0% [93·9 to 97·4]; difference 0·48 percentage points [–1·61 to 2·88]). 3 h after treatment, headache (n=50 [8%]) and vertigo (n=37 [6%]) were the most widely reported symptoms; 24 h after treatment, 50 (8%) patients reported vertigo and 41 (7%) reported headache. Mainly mild adverse events were reported with peak numbers (n=111 [18%]) at 24 h after treatment. Three participants had moderate adverse events 3 h after treatment: two (<1%) had vertigo and one (<1%) had headache, and two had moderate adverse events 24 h after treatment: one (<1%) had vomiting and one (<1%) had vomiting plus diarrhoea. Interpretation: Tribendimidine in combination with either ivermectin or oxantel pamoate had a similar, non-inferior efficacy profile as albendazole plus oxantel pamoate, hence tribendimidine will be a useful addition to the depleted anthelmintic drug armamentarium. Funding: Swiss National Science Foundation.